Intergroup Contact Is Associated with Less Negative Attitude toward Women Managers: The Bolstering Effect of Social Dominance Orientation - Federico Contu; Alessio Tesi; Antonio Aiello (Behavioral Sciences, 2023)
This cross-sectional study examined the intergroup contact hypothesis in the workplace by enrolling 150 Italian employees. Within the framework of social dominance theory, the purpose of this study was to test the assumption that individuals with higher levels of social dominance orientation are more likely to exhibit prejudice against women in managerial positions and benefit more from intergroup contact with a female supervisor. In particular, we found that individuals with higher levels of social dominance orientation exhibited more negative attitudes towards women in manager positions, but this effect only appeared when their superiors were women, as opposed to men. In addition, participants with higher social dominance orientation experienced more positive outcomes from intergroup contact, resulting in less negative attitudes toward women managers, than those with lower social dominance orientation. Overall, these findings yield insights into how intergroup contact affects individuals with prejudice tendencies, indicating that contact with the targeted group (i.e., women in managerial positions) is negatively associated with negative attitudes towards the group, even when the prejudice is driven by social dominance orientation. These results could shed light on new routes to design practical intervention aimed at solving prejudice towards women in leadership roles.